Identification and clinical significance of nodular regenerative hyperplasia in primary sclerosing cholangitis. Issue 9 (19th July 2022) - Ozturk, Nazli Begum; Fiel, Maria Isabel; Schiano, Thomas D.
Abstract: Background and Aim: Primary sclerosing cholangitis (PSC) is a chronic cholestatic liver disease characterized by inflammation and fibrosis of intrahepatic and extrahepatic bile ducts. PSC is frequently associated with inflammatory bowel disease (IBD). Nodular regenerative hyperplasia (NRH) can occur in IBD with the use or even in the absence of thiopurine treatment. We aimed to study the significance of the presence of NRH and obliterative portal venopathy (OPV), both causes of non‐cirrhotic portal hypertension (NCPH), in patients having PSC. Methods: Patients with PSC and concurrent NRH on liver biopsy were identified from the digital pathology database covering the period 2003–2019. Evaluation of liver biopsy and the original diagnoses were confirmed on review based on standard histological features diagnostic for NRH and OPV. Clinical and laboratory data were obtained from electronic medical records. Results: Thirty‐one patients (21 male, 10 female; median age at biopsy 40.1 years) were included in the study. Twelve (38.7%) patients had OPV in addition to NRH on the liver biopsy. Nineteen (61.2%) patients had IBD including 11 with Crohn's disease (CD), 7 with ulcerative colitis (UC), and 1 with indeterminate colitis. Thirteen (41.9%) patients had evidence of portal hypertension, 10 (32.2%) with esophageal varices, 4 (12.9%) with history of variceal bleeding, 6 (19.3%) with ascites, and 14 (12.9%) with splenomegaly. Eleven (35.4%) patients had a cirrhotic‐appearing liver on imaging. Twelve (38.7%) patients had a history of prior or current thiopurine use. Conclusions: The current study suggests that NRH with or without OPV independently occurs in patients having PSC and may lead to NCPH, even in the absence of concurrent IBD and/or thiopurine therapy. Abstract : Nodular regenerative hyperplasia (NRH) can be present in primary sclerosing cholangitis (PSC) independent from having inflammatory bowel disease or use of thiopurine therapy. NRH can mimic cirrhosis on imaging studies. Identification of NRH in PSC is important as it might be the cause of portal hypertension.